Comparative transcriptome and expression profiling of resistant and susceptible banana cultivars during infection by Fusarium oxysporum - Kaushal, M.; Mahuku, George S.; Swennen, Rony L. (MDPI, 2021)
Fusarium wilt caused by Fusarium oxysporum f. sp. cubense (Foc) is one of the most destructive diseases of banana. Methods to control the disease are still inadequate. The present investigation targeted expression of defense-related genes in tissue cultured banana plantlets of Fusarium resistant and susceptible cultivars after infection with biological control agents (BCAs) and Fusarium (Foc race 1). In total 3034 differentially expressed genes were identified which annotated to 58 transcriptional families (TF). TF families such as MYB, bHLH and NAC TFs were mostly up-regulated in response to pathogen stress, whereas AP2/EREBP were mostly down-regulated. Most genes were associated with plant–pathogen response, plant hormone signal transduction, starch and sucrose metabolism, cysteine and methionine metabolism, flavonoid biosynthesis, selenocompound metabolism, phenylpropanoid biosynthesis, mRNA surveillance pathway, mannose type O-glycan biosynthesis, amino acid and nucleotide sugar metabolism, cyanoamino acid metabolism, and hormone signal transduction. Our results showed that the defense mechanisms of resistant and susceptible banana cultivars treated with BCAs, were regulated by differentially expressed genes in various categories of defense pathways. Furthermore, the association with different resistant levels might serve as a strong foundation for the control of Fusarium wilt of banana.